3 - Les collaborations université-industrie en Afrique* - Masinda, Mambo Tabu (Journal of Higher Education in Africa, 2006)
This article explores university–industry linkages as a strategy for industrialization in Africa. It presents the advantages of cooperation between university and industry to highlight the importance of collective learning through the sharing of knowledge and resources. The author primarily aims to elicit debate on the strengths and limi- tations of African universities in collaborating with national and multinational cor- porations. The article first describes the cultures of both the university and industry, analyses different experience of university–industry collaboration in countries of varying levels of science and technology development and lastly suggests action framework adapted to the realities of industries and universities in Africa.